(untitled) (LEGAL DIALOGICA, 2025)
This study aims to analyze law enforcement against online gambling crimes in Makassar City, particularly through a case study conducted at the South Sulawesi Regional Police. In the digital era, online gambling is increasingly prevalent and poses a significant challenge to law enforcement in Indonesia. This study uses an empirical legal approach with surveys and interviews with perpetrators, victims, and investigators. This research employed empirical research methods. Data collection involved fieldwork and literature review through interviews. Data were processed systematically, factually, and accurately, analyzed qualitatively, and presented descriptively. The research findings indicate that law enforcement still faces various obstacles, including a lack of understanding of information technology among law enforcement officials. Furthermore, social and economic factors contribute to the rise in online gambling practices, particularly among the younger generation. The study found that despite existing regulations, the effectiveness of law enforcement against online gambling remains low, leading to a lack of deterrence among many perpetrators. The analysis suggests the need to increase human resource capacity in cybercrime units, as well as conduct public education campaigns on the risks of online gambling. This research is expected to contribute to the development of more effective law enforcement policies and practices in addressing online gambling in Indonesia. Abstrak: Penelitian ini bertujuan untuk menganalisis penegakan hukum terhadap tindak pidana perjudian online di Kota Makassar, terutama melalui studi kasus yang dilakukan di Polda Sulawesi Selatan. Dalam era digital, perjudian online semakin marak dan menjadi tantangan signifikan bagi penegakan hukum di Indonesia. Penelitian ini menggunakan pendekatan hukum empiris dengan metode survei dan wawancara kepada pelaku, korban, dan penyidik. Penelitian ini menggunakan metode penelitian empiris. Metode pengumpulan data dilakukan menggunakan studi lapangan dan studi kepustakaan dengan cara wawancara. Data diolah secara sistematis, faktual, dan akurat serta dianalisis secara kualitatif dan disajikan secara deskriptif. Hasil penelitian menunjukkan bahwa penegakan hukum masih menghadapi berbagai kendala, termasuk kurangnya pemahaman aparat penegak hukum mengenai teknologi informasi. Selain itu, faktor sosial dan ekonomi berkontribusi pada meningkatnya praktik perjudian online, terutama di kalangan generasi muda. Penelitian ini menemukan bahwa meskipun regulasi sudah ada, efektivitas penegakan hukum terhadap perjudian online masih rendah, yang menyebabkan banyak pelaku tidak merasa jera. Dari hasil analisis, disarankan agar diperlukan peningkatan kapasitas sumber daya manusia di unit cyber crime, serta kampanye edukasi masyarakat tentang risiko perjudian online. Penelitian ini diharapkan dapat memberikan kontribusi terhadap pengembangan kebijakan dan praktik penegakan hukum yang lebih efektif dalam menghadapi perjudian online di Indonesia.